A review of Sb2Se3 photovoltaic absorber materials and thin-film solar cells - Mavlonov, Abdurashid; Razykov, Takhir; Raziq, Fazal; Gan, Jiantuo; Chantana, Jakapan; Kawano, Yu; Nishimura, Takahito; Wei, Haoming; Zakutayev, Andriy; Minemoto, Takashi; Zu, Xiaotao; Li, Sean; et al. (Solar Energy, 2020)
Energy generated from environmentally friendly, cost-effective solar cells is a key aspect for developing a clean renewable-energy economy. Non-toxic and Earth-abundant materials with high absorption coefficient (>105 cm−1) and optimal bandgap (1–1.5 eV) have received great attention as photovoltaic (PV) absorber layers during the last few decades. Among them, antimony selenide (Sb2Se3) has been a promising PV absorber, with steadily increasing power-conversion efficiency (PCE) compared to other emerging compounds. Very recent studies showed that high-quality ZnO:Al/ZnO/CdS/TiO2/Sb2Se3/MoSe2/Mo devices with PCE of 9.2% can be fabricated using cost-effective novel compounds. Considering these recent advances, this article provides an overview of the material properties of Sb2Se3 thin films and the recent progress made with Sb2Se3-based solar cells. Analysis of Sb2Se3-based thin-film solar cells has also shown that the devices have relatively good light management due to their suitable bandgap and high absorption coefficient, whereas carrier management, i.e. collection efficiency of photo-generated carriers, needs significant improvement. Overall, this study provides background knowledge on material properties and device performance and suggests main research directions to overcome the limiting factors of solar cell performance.